Current insight on the mechanisms of programmed cell death in sepsis-induced myocardial dysfunction - Liu, An-Bu; Li, Shu-Jing; Yu, Yuan-Yuan; Zhang, Jun-Fei; Ma, Lei (Frontiers in Cell and Developmental Biology, 2023)
Sepsis is a clinical syndrome characterized by a dysregulated host response to infection, leading to life-threatening organ dysfunction. It is a high-fatality condition associated with a complex interplay of immune and inflammatory responses that can cause severe harm to vital organs. Sepsis-induced myocardial injury (SIMI), as a severe complication of sepsis, significantly affects the prognosis of septic patients and shortens their survival time. For the sake of better administrating hospitalized patients with sepsis, it is necessary to understand the specific mechanisms of SIMI. To date, multiple studies have shown that programmed cell death (PCD) may play an essential role in myocardial injury in sepsis, offering new strategies and insights for the therapeutic aspects of SIMI. This review aims to elucidate the role of cardiomyocyte’ s programmed death in the pathophysiological mechanisms of SIMI, with a particular focus on the classical pathways, key molecules, and signaling transduction of PCD. It will explore the role of the cross-interaction between different patterns of PCD in SIMI, providing a new theoretical basis for multi-target treatments for SIMI.